BRD4-targeting PROTAC as a unique tool to study biomolecular condensates - Shi, Yi; Liao, Yuan; Liu, Qianlong; Ni, Zhihao; Zhang, Zhenzhen; Shi, Minglei; Li, Pilong; Li, Haitao; Rao, Yu (Cell discovery, 2023)
Biomolecular condensates play key roles in various biological processes. However, specific condensation modulators are currently lacking. PROTAC is a new technology that can use small molecules to degrade target proteins specifically. PROTAC molecules are expected to regulate biomolecular condensates dynamically by degrading/recovering key molecules in biomolecular condensates. In this study, we employed a BRD4-targeting PROTAC molecule to regulate the super-enhancer (SE) condensate and monitored the changes of SE condensate under PROTAC treatment using live-cell imaging and high-throughput sequencing technologies. As a result, we found that BRD4-targeting PROTACs can significantly reduce the BRD4 condensates, and we established a quantitative method for tracking BRD4 condensates by PROTAC and cellular imaging. Surprisingly and encouragingly, BRD4 condensates were observed to preferentially form and play specialized roles in biological process regulation for the first time. Additionally, BRD4 PROTAC makes it possible to observe the dynamics of other condensate components under the continued disruption of BRD4 condensates. Together, these results shed new light on research methods for liquid-liquid phase separation (LLPS), and specifically demonstrate that PROTAC presents a powerful and distinctive tool for the study of biomolecular condensates.